The Value of IGF-1 and IGFBP-1 in Patients With Heart Failure With Reduced, Mid-range, and Preserved Ejection Fraction - Guo, Shaohua; Gong, Mengqi; Tse, Gary; Li, Guangping; Chen, Kang-Yin; Liu, Tong (Frontiers in Cardiovascular Medicine, 2022)
Background: Previous studies have reported inconsistent results regarding the implications of deranged IGF1/IGFBP-1 axis in heart failure (HF) patients. This study evaluated the roles of IGF1/IGFBP-1 axis in HF patients with reduced ejection fraction (HFrEF), mid-range ejection fraction (HFmrEF), or preserved ejection fraction (HFpEF). Methods: Consecutive patients with HFrEF, HFmrEF and HFpEF who underwent comprehensive cardiac assessment were included. The primary endpoint was the composite endpoint of all-cause death and HF rehospitalization at one year. Results: A total of 151 patients with HF (HFrEF: n= 51; HFmrEF: n= 30; HFpEF: n=70) and 50 control subjects were included. The concentrations of IGFBP-1 (P<0.001) and IGFBP-1/IGF-1 ratio (P<0.001) were significantly lower in HF patients compared to controls and can readily distinguish patients with and without HF (IGFBP-1: AUC:0.725, P < 0.001; IGFBP-1/IGF-1 ratio: AUC:0.755, P < 0.001; respectively). The concentrations of IGF-1, IGFBP-1, and IGFBP-1/IGF-1 ratio were similar among HFpEF, HFmrEF, HFrEF patients. IGFBP-1 and IGFBP-1/IGF-1 ratio positively correlated with NT-proBNP levels (r =0.255, p = 0.002; r = 0.224, P = 0.007, respectively). IGF-1, IGFBP-1, and IGFBP-1/IGF-1 ratio were not predictive of primary endpoint at one year for the whole HF patients and HF subtypes on univariable or multivariable Cox regression. Conclusions: The concentrations of plasma IGFBP-1 and IGFBP-1/IGF-1 ratio can distinguish patients with and without HF. In HF, IGFBP-1 and IGFBP-1/IGF-1 ratio positively correlated with NT-proBNP levels.